M-mode ultrasound evaluation of lateral abdominal muscle postural response to load: an exploratory study - Biały Maciej; Adamczyk Wacław Marceli; Stranc Tomasz; Szlachta Grzegorz; Gnat Rafał (Journal of Ultrasonography)
There is a need to evaluate the tissue deformation index of lateral abdominal muscles using M-mode ultrasound in a cohort of healthy subjects to establish a convenient reference point for clinical reasoning in patients. The aim of the study was to assess differences in the tissue deformation index between individual lateral abdominal muscles regardless of body side, compare these differences in the tissue deformation index on the right and left sides of the body, and evaluate side-to-side differences in the tissue deformation index within individual lateral abdominal muscles.